Pengaruh Harga Jual Dan Kualitas Makanan Terhadap Kepuasan Pelanggan Pada Rumah Makan Pondok NQ (Nurul Qomar) Seafood Kota Palembang - Muhamad Ridho; Hilda Hilda; Iceu Sri Gustiana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Eating and drinking are the most basic needs of all living creatures, including humans. because eating and drinking is one of the primary needs or basic needs that must be met every day and is a top priority that must be fulfilled by every human being. Therefore, many entrepreneurs have established restaurants, one of which is the Nurul Qomar Islamic Boarding School which has established a seafood culinary restaurant called Pondok NQ Seafood Restaurant. The aim of this research is to find out how the selling price and food quality influence customer satisfaction at the Pondok Seafood NQ (Nurul Qomar) Restaurant, Palembang City. This type of research uses quantitative methods. The population in this study were consumers of Pondok NQ Seafood restaurants, which according to data numbered 11,000. Sampling was taken using the Slovin technique as many as 100 respondents. This research uses primary data and secondary data, as well as distributing questionnaires with a Likert scale. Based on the research results, the selling price influences customer satisfaction. Food quality influences customer satisfaction. And the selling price and food quality simultaneously have a significant effect on customer satisfaction at the Pondok NQ Seafood restaurant in the city of Palembang.